Adaptive Assessment in Islamic Religious Education Learning for Students with Special Needs High School - Lismaya, Siti Sopa; Sumarna, Elan; Anwar, Saepul (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
This study examines the implementation of assessment practices in Islamic Religious Education at Senior High Schools for Students with Special Needs in Bandung and Cimahi, Indonesia, using a qualitative, collective case study design. The data were collected through in-depth interviews, classroom observations, and document analysis of lesson plans and assessment instruments involving six Islamic Religious Education teachers from five special senior high schools, selected purposively. Data were analyzed through data reduction, data display, and thematic conclusion drawing, applying triangulation of sources and techniques to ensure trustworthiness. The findings indicate that assessment practices were implemented adaptively, considering the characteristics and learning students with special needs across the cognitive, affective, and psychomotor domains. Assessment results were used to inform instructional follow-up, strengthen student motivation, and support reflective improvement of teaching strategies. This study contributes to a deeper understanding of contextual and sustainable assessment practices in Islamic Religious Education for students with disabilities and provides recommendations for policy development and teacher professional development in inclusive assessment practices.